The electromagnetic property of chemically reduced graphene oxide and its application as microwave absorbing material - Wang, Chao; Han, Xijiang; Xu, Ping; Zhang, Xiaolin; Du, Yunchen; Hu, Surong; Wang, Jingyu; Wang, Xiaohong (Applied physics letters, 2011)
The residual defects and groups in chemically reduced graphene oxide cannot only improve the impedance match characteristic and prompt energy transition from contiguous states to Fermi level, but also introduce defect polarization relaxation and groups' electronic dipole relaxation, which are all in favor of electromagnetic wave penetration and absorption. The chemically reduced graphene oxide shows enhanced microwave absorption compared with graphite and carbon nanotubes, and can be expected to display better absorption than high quality graphene, exhibiting a promising prospect as microwave absorbing material.